2016
DOI: 10.4172/2329-9002.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Genealogy of the Genome Components in the Highly Homogeneous Pandemic Vibrio parahaemolyticus Population

Abstract: Bacterial genomes evolve through two different mechanisms: 1) changes in or occasional loss of ancestral genes, which preserve the founder clonal genealogy or frame, and 2) sporadic gains of new genes via horizontal gene transfer, which introduces DNA with a different genealogy or clonal frame. Evolution has led to the emergence of a pathogenic strain pandemic of Vibrio parahaemolyticus, which has propagated globally, causing large outbreaks of seafood-associated diarrhea. The low sequence diversity of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Early analysis of a few genes ( tdh , trh , orf8 , and toxRS ) and molecular techniques applied to isolates with serotype O3:K6 obtained after 1996 showed that they were undifferentiated, and the population was considered clonal (genes deriving from a same common ancestor) even though only a few genes were tested. Later analysis using a large number of isolates and techniques with higher resolution such as RFLP-PFGE ( Chowdhury et al, 2000 ), direct genome restriction enzyme analysis (DGREA) by conventional gel electrophoresis ( Fuenzalida et al, 2006 ), multilocus sequence typing (MLST) ( Chowdhury et al, 2004 ; González-Escalona et al, 2008 ; Chao et al, 2011 ), multilocus variable-number tandem-repeat analysis (MLVA) ( Kimura et al, 2008 ; García et al, 2012 ), microarray analysis ( Izutsu et al, 2008 ) and finally whole-genome sequencing ( Chen et al, 2011 ; Loyola et al, 2015 , 2016 ), confirmed the clonal nature of the group. However, these techniques also showed the existence of variants that were considered evolutionary products of the initial clone, and showed numerous cases of genomic regions with numerous SNVs indicating origin from a different ancestor.…”
Section: Evolution Of the Pandemic Strainmentioning
confidence: 99%
See 4 more Smart Citations
“…Early analysis of a few genes ( tdh , trh , orf8 , and toxRS ) and molecular techniques applied to isolates with serotype O3:K6 obtained after 1996 showed that they were undifferentiated, and the population was considered clonal (genes deriving from a same common ancestor) even though only a few genes were tested. Later analysis using a large number of isolates and techniques with higher resolution such as RFLP-PFGE ( Chowdhury et al, 2000 ), direct genome restriction enzyme analysis (DGREA) by conventional gel electrophoresis ( Fuenzalida et al, 2006 ), multilocus sequence typing (MLST) ( Chowdhury et al, 2004 ; González-Escalona et al, 2008 ; Chao et al, 2011 ), multilocus variable-number tandem-repeat analysis (MLVA) ( Kimura et al, 2008 ; García et al, 2012 ), microarray analysis ( Izutsu et al, 2008 ) and finally whole-genome sequencing ( Chen et al, 2011 ; Loyola et al, 2015 , 2016 ), confirmed the clonal nature of the group. However, these techniques also showed the existence of variants that were considered evolutionary products of the initial clone, and showed numerous cases of genomic regions with numerous SNVs indicating origin from a different ancestor.…”
Section: Evolution Of the Pandemic Strainmentioning
confidence: 99%
“…Whole-genome sequence analysis of three pandemic isolates, including one with a different serotype (O4:K68) ( Chen et al, 2011 ), showed high similarity along the whole genome in this clonal complex except in the O- and K-antigen-encoding gene clusters, which contained 94% of the SNVs. Later, in ClonalframeML analysis of whole genomes, the O and K coding regions were identified as recombinant regions in three pandemic isolates with a serotype other than O3:K6 ( Loyola et al, 2016 ). These and other less direct observations indicated that serotype conversion was due to a recombination or gene conversion event.…”
Section: Evolution Of the Pandemic Strainmentioning
confidence: 99%
See 3 more Smart Citations